al-Masa’il al-Nahwiyyah (Dirasah Taqabuliyyah Baina Madrasah al-Bashrah wa al-Kufah) - Roviin Roviin (Jurnal Alsinatuna, 2018)
When Islam spread to the Arabian Peninsula, the Arabs were also scattered, communicating with non-Arabs and mixing with each other. As a result, a new generation emerged that could not preserve the authenticity of its language. Therefore, the Arabs became distorted from the authenticity of their language. The emergence of many of these irregularities led to the need to preserve the originality of the Arabic language, and Abu al-Aswad al-Duwali was the first who establish Arabic grammar on the orders of Caliph Ali ibn Abi Talib. After Abu al-Aswad al-Duwali, emerging famous grammars were divided into madrasa of Bashra and Kufa, each madrasa had characteristics and differences. The differences between these two madrasas is enormous and in many cases. The prominent difference is that the madrasa of Bashra is more stringent in Arabic grammar, while the madrasa of Kufa is looser.